MENINGKATKAN MOTIVASI BELAJAR MELALUI LAYANAN BIMBINGAN KELOMPOK SISWA KELAS VII 2 SMPN 1 TELUK KUANTAN - Nurmiana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports research that applies group guidance services to increase students’ learning motivation. Group guidance service is an attempt for helping students to solve their problems by utilizing the group dynamic. If a group dynamic can be made properly, then group members will help each other, accept, and be empathic sincerely. Motivation is the process of giving encouragement, direction, and behavior implementation. Therefore, motivation is a behavior that has full of energy, has been directed, and has lasted a long time. This motivation encourages someone to do a job or activity like learning. The research was a Classroom Action Research (CAR) using a research design model of Kemmis and Mc. Taggart and was held at SMPN 1 Teluk Kuantan. The research subjects were 27 students, which consisted of 13 male and 14 female students. The general description of students’ learning motivation in the first cycle was only seven of 27 students who have high learning motivation with a percentage of 25.92%. Whilst the general description of students’ learning motivation in the second cycle increased significantly was students who have high learning motivation with a percentage of 33.33% from nine students. Activity and students’ learning motivation results in the first cycle with a score of 65 was only 59.25%, while in the second cycle with a score of 65 achieved to a significant percentage of 81.48%. It proves that there was an increased result of 22.23% from cycle I to cycle II.